Guinea- Bissau : Fifth Review Under the Extended Credit Facility Arrangement, Request for Extension and Augmentation of Access, and Financing Assurances Review-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Guinea-Bissau's Fifth Review Under the Extended Credit Facility (ECF) Arrangement, Requests for Extension and Augmentation of Access, and Financing Assurances Review. Program implementation for the fifth review has been good. All performance criteria and indicative targets were met, as were six of eight structural benchmarks, with one of the remaining two benchmarks subsequently completed and the other under way. Economic activity has remained robust. Real GDP grew by an estimated 5.9 percent in 2017, with consumer price inflation of 1.1 percent and an external current account deficit of 0.5 percent of GDP. The IMF staff supports completion of the fifth review under the ECF arrangement, extension of the arrangement, and augmentation of access.